ECCLESIA IN ASIA ANUGERAH BAGI MISI GEREJA ASIA - Hariprabowo, Yacobus (UNIKA Santo Thomas, 2004)
The mission activity in the largest continent of the world faces many problems. Asia has diversity in the races, peoples, culture, mentality, languages and ancient religions. Asian religions are highly developed and permeate the whole texture of peoples’ spiritual and cultural life. The history of the christian mission in Asia goes back to the first century. In fact Jesus and Christianity were born in Asia. However, Christianity at present is still a minority in its birth place. In the third millennium, the mission in Asia is just beginning. In the first place the Asian Churches are no more objects of mission but subjects. New mission theology, theology of religions and contextual theologies are gradually emerging. The Special Assembly for Asia of the Synod of the Asian bishops, and the Apostolic Exhortation Ecclesia in Asia of John Paul II, gives priority to the encounter of Christianity with the cultures and ancient religions of this continent, characterizing the specific challenge that evangelisation meets there.